2015
DOI: 10.1039/c4cp03755c
|View full text |Cite
|
Sign up to set email alerts
|

Coverage-dependent thermodynamic analysis of the formation of water and hydrogen peroxide on a platinum model catalyst

Abstract: Understanding the selectivity of the oxygen reduction reaction, especially the formation of water versus hydrogen peroxide in fuel cells, is an ongoing challenge in electrochemistry, surface science and catalysis. In this study, we propose a comprehensive thermodynamic analysis of the reaction intermediates for the formation of water on Pt(111). Density functional theory calculations of all the elementary steps linking hydroxyl and hydroperoxyl surface species with water and hydrogen peroxide have been perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
(241 reference statements)
2
18
0
1
Order By: Relevance
“…Apart from the 4 e – reduction of oxygen to form H 2 O (eq 6), oxygen reduction can also proceed through the 2e – pathway in which the intermediate OOH* reduces to hydrogen peroxide (H 2 O 2 ) . Hydrogen peroxide (H 2 O 2 ), though undesirable in a fuel cell, is a strong and environmentally benign oxidizing agent. , Therefore, understanding the selectivity of the 2e – and the 4 e – ORR is beneficial. The associate 2 e – ORR can be written as follows: The adsorption energies of the intermediate OOH* calculated in the 4e – ORR model could be directly used to understand the 2e – oxygen reduction to hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the 4 e – reduction of oxygen to form H 2 O (eq 6), oxygen reduction can also proceed through the 2e – pathway in which the intermediate OOH* reduces to hydrogen peroxide (H 2 O 2 ) . Hydrogen peroxide (H 2 O 2 ), though undesirable in a fuel cell, is a strong and environmentally benign oxidizing agent. , Therefore, understanding the selectivity of the 2e – and the 4 e – ORR is beneficial. The associate 2 e – ORR can be written as follows: The adsorption energies of the intermediate OOH* calculated in the 4e – ORR model could be directly used to understand the 2e – oxygen reduction to hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In HSABs, ORR is a process of oxygen adsorption and catalytical reaction. A full reduction is a dissociative adsorption process, which begins with O2 adsorption on a catalyst surface [44,45]. The detailed ORR mechanism ( Fig.…”
Section: Electrochemical Reactions In Hsabmentioning
confidence: 99%
“…Classical microkinetic models were grounded on mean-field theory. It was found that the coverage effect plays a vital role in determining the reaction mechanism in our previous works. , Models that do not consider the coverage effect may fail to explain the reaction mechanisms found in experiments. , , Undeniably, a deeper mechanism investigation on the direct synthesis of H 2 O 2 , including coverage effects, needs to be performed to accomplish a substantial breakthrough for this system. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…57,[68][69][70]80 Undeniably, a deeper mechanism investigation on the direct synthesis of H 2 O 2 , including coverage effects, needs to be performed to accomplish a substantial breakthrough for this system. 27,31,65,66 In this work, we carry out the first detailed investigation of the reaction mechanisms for the direct synthesis of H 2 O 2 using the DFT-D3 functional and state-of-the-art microkinetic modeling 70,72 on three pure metal surfaces (Pd(111), Au(111), and Cu(111)) and two typical alloyed Pd surfaces (PdHg and PdAu). To be closer to the realistic conditions, the most challenging factor, lateral interactions (coverage effects) in kinetic modeling are explicitly taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation